2001
DOI: 10.1016/s0022-4405(01)00071-1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Flynn Effect Affect IQ Scores of Students Classified as LD?

Abstract: This research examined two samples of students classified as learning disabled (LD) for evidence of the phenomenon known as the Flynn effect (FE;Flynn, 1999). Triennial test data were collected for two samples. Sample 1 included students tested twice with the Wechsler Intelligence Scale for Children-Third Edition (WISC-III; n ϭ 59). Sample 2, the primary data set, included students tested first with the Wechsler Intelligence Scale for Children-Revised (WISC-R), and then with the WISC-III ( n ϭ 171). A secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
5
16
1
5
Order By: Relevance
“…Kanaya and Ceci (2012) recently investigated the potential effects of the FE on the diagnosis of specific learning disorders. This research, similar to previous studies (Gaskill & Brantley, 1996;Truscott & Frank, 2001), used logistic regression analyses for examining the changes in diagnoses of learning disability across time after a new assessment. This study showed a significant decrease in the number of children eligible for special education programs, partially due to the FE.…”
Section: Implications For the Identification Of Learning And Intellecmentioning
confidence: 94%
“…Kanaya and Ceci (2012) recently investigated the potential effects of the FE on the diagnosis of specific learning disorders. This research, similar to previous studies (Gaskill & Brantley, 1996;Truscott & Frank, 2001), used logistic regression analyses for examining the changes in diagnoses of learning disability across time after a new assessment. This study showed a significant decrease in the number of children eligible for special education programs, partially due to the FE.…”
Section: Implications For the Identification Of Learning And Intellecmentioning
confidence: 94%
“…Some researchers have found that the Flynn effect is uniform across the borderline (Full Scale IQ 70–80) and mental retardation (Full Scale IQ <70) intellectual ability levels (Kanaya et al. 2001; Truscott & Frank 2001), but others have found it to be smaller in those with lower IQ, and that it can even reverse for those with scores in the learning disability range (Spruill & Beck 1988; Spitz 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Truscott & Frank (2001) analysed the Wechsler Intelligence Scale for Children‐Revised (WISC‐R; Wechsler 1974) and the more recent Wechsler Intelligence Scale for Children‐Third Edition (WISC‐III; Wechsler 1991) scores for a sample of children receiving special education because of learning difficulties ( n = 171). However, only children with an IQ of 80 or more were included in the sample, as Spitz 1989 reported an atypical effect of the Flynn effect in children with mental retardation (children with a diagnosis of mental retardation typically have a Full Scale IQ of <70).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flynn and others have documented an upward drift in normative performances on intelligence tests (Carlton & Sapp, 1997;Flynn, 1985Flynn, , 1987Truscott & Frank, 2001.). Known as the "Flynn effect," these score increases in the United States amount to approximately three points per decade.…”
mentioning
confidence: 99%